2009
DOI: 10.1099/vir.0.002105-0
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of a viral antigen to invariant chain leads to augmented T-cell immunity and improved protection in gene-gun DNA-vaccinated mice

Abstract: It has recently been demonstrated that a recombinant replication-deficient human adenovirus 5 (Ad5) vector expressing lymphocytic choriomeningitis virus (LCMV) glycoprotein (GP) fused to the p31 invariant (Ii) chain confers broad, long-lasting T-cell immunity that completely protects C57BL/6 mice against lethal peripheral challenge. The current study questioned whether the same strategy, i.e. linkage of GP to an Ii chain, could be applied to a naked DNA vaccine. Following gene-gun immunization with the linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
1
11
2
Order By: Relevance
“…We found that linkage of Ii to HCV NS3 enhanced, accelerated, and broadened the CD8 + T cell response in a similar manner as seen in the LCMV model (28,40). The Ad-IiNS3-induced CD8 + T cell frequencies shown in this study are, to our knowledge, considerably higher than any of the previously published frequencies obtained after vaccination with HCV NS proteins (17)(18)(19)(20).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…We found that linkage of Ii to HCV NS3 enhanced, accelerated, and broadened the CD8 + T cell response in a similar manner as seen in the LCMV model (28,40). The Ad-IiNS3-induced CD8 + T cell frequencies shown in this study are, to our knowledge, considerably higher than any of the previously published frequencies obtained after vaccination with HCV NS proteins (17)(18)(19)(20).…”
Section: Discussioncontrasting
confidence: 54%
“…In conclusion, our laboratory has shown previously that Iilinkage of the vaccine Ag could enhance, broaden, accelerate, and prolong CD4 + and CD8 + T cell responses toward the model virus LCMV independent of vaccination platform (28,40). The current study further explored the benefits of the Ii linkage technology by applying it to an Ag of human disease relevance, HCV NS3, which moreover is well known for its low immunogenicity (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…The MHC class II associated invariant chain linked antigen concept was also tested as a DNA vaccine, and found to increase CD8+ T cell responses working both alone and as a primer for an adenoviral boost. Moreover, the MHC class II associated Invariant chain linked antigen concept was also beneficial when applied in the booster supporting the conclusion that increased direct presentation benefits adenovirus induced CD8+ T cell responses after the initial priming (Grujic et al, 2009). …”
Section: Role Of Cd4+ T Cell Helpmentioning
confidence: 50%
“…The use of DNA priming is logical and results in a broadening of the CD4+ T cell response, an increase in the IL-2 competence of the primed CD8+ T cells and improved protection after SIV challenge (Casimiro et al, 2005;Cox et al, 2008;Wu et al, 2005). Please note that although some animal studies point to an improved immunogenicity of DNA primed adenovirus immunizations (Grujic et al, 2009), this has not been verified in humans (Bett et al, 2010). Although DNA primed adenovirus immunization have shown some promise, it pales in comparison to the recent pre-clinical results obtained using adenoviruses of different serotypes (Liu et al, 2009) or adenovirus as primers for MVA vectors (ReyesSandoval et al, 2010).…”
Section: Use Of Adenovirus In Heterologous Prime-boost Regimensmentioning
confidence: 99%
“…For this reason, there have been a large number of studies aimed at enhancing the DNA vaccine through the improving of the DNA delivery systems and DNA sequence (codon optimization and/or fusion with other genes for the improvement of vaccinal antigens) [70][71][72][73][74][75][76][77][78].…”
Section: Genetic Immunization: Promising Resultsmentioning
confidence: 99%